Inhibitors of e-learning in engineering education: an interpretive structural modelling approach. (21st November 2021) - Pramod, V.R.; Devadasan, S.R.; Murugesh, R.
Despite being a useful instrument, e-learning has not been effectively adopted in engineering education. The adoption of e-learning process in engineering education has been subjected to various inhibitors. This situation indicates the need to identify the inhibitors of adopting e-learning in engineering education and their relationships. In order to fulfil the need, the research reported in this paper has been carried out. In this regard two research questions have been framed. First research question was framed to examine the influence of inhibitors for the adoption of e-learning in engineering education. Second research question was developed to examine the synergic influence of inhibitors for the adoption of e-learning in engineering education. This examination was conducted by applying Interpretive Structural Modelling (ISM) approach. In the beginning, ten inhibitors of adopting e-learning in engineering education were gathered by interviewing educational leaders. Subsequently, by referring to these inhibitors, ISM was applied. The outcome of this endeavour indicated that out of the ten inhibitors, seven inhibitors play powerful role in preventing the adoption of e-learning process in engineering education. Among these, financial constraint was found to be playing a powerful role in inhibiting the adoption e-learning process in engineering education.